The Community of Mixed Skin Plants (Calligoneta CaputMedusa, C. Leucocladum) and Their Distribution in the Red Desert (Texas Journal of Agriculture and Biological Sciences, 2023)
Under certain conditions, often in secondary living conditions, juzug as a dominant or subdominant plant participates in the formation of almost all communities of psammophilic plants. Juzgun can be a shrub or tree up to 2.5 (5) m high, depending on growing conditions, dominating the first or second tier (story) in most communities, the growing season of the plant begins in March it blooms in April, bears fruit at the end of May, and stops growing with the onset of autumn frosts. The absorptive leaves begin to shed at the same time as the fruits in some hot and drought years, but in years of sufficient moisture, the thin stringy leaves may persist until late fall. Seeds that remain underground in winter begin to germinate in early spring. In most species, seed germination is maintained for 5-9 years, taking into account the spread of the fruits of the plant by the wind, only those that fall into favorable conditions can germinate